Source areas of North Cordilleran endemic plants: evidence from Sheep and Outpost Mountains, Kluane National Park, Yukon Territory - Harris, Stuart A. (ERDKUNDE, 2004)
When Late Wisconsin ice sheets inundated most of Canada, they destroyed the pre-existing vegetation along a 1600 km north-south section of the Canadian Cordillera. The vegetation next to these ice masses had to adapt to great climatic changes, and part of this adaptation resulted in the evolution of new species (Hultén, 1968). During deglaciation, the vegetation migrated back into the previously glaciated areas, but the new species usually experienced more difficulty in colonizing the deglaciated areas due to being adapted to specific environmental conditions. As a result, their present-day distribution is centred on the area in which they evolved, whereas the rest of the flora had been selected and were adapted to survive under a wider range of environmental conditions. One of these areas of speciation lay on the eastern margin of Beringia on the north and northwest flank of the former Cordilleran ice sheets. Kluane Lake lies just within the glaciated zone and is therefore a good place to explore the numbers and presence of the new species. The elevational distribution of vascular plants is described for a NW-SE transect across the Slims River valley from the top of Sheep Mountain to the top of Outpost Mountain, at Kluane Lake, Yukon Territory (61? 01' N, 138?24' W.). Ten percent of the taxa are local species endemic to the North Cordillera, regardless of vegetation zone or aspect. Aspect altered the total number of species on a mountain and also the vegetation zonation, but not the percentage of taxa from a given geographic source. An analysis of the known distribution of North Cordilleran species indicates that there are three main centres of speciation, of which the rain-shadow area north of the Wrangell - St. Elias Range is the most important (69 taxa or 72% of the total species). The others are the Brooks Range and north Yukon mountains (13 taxa) and the Kenai Peninsula, Alaska (12 taxa).